Increased expression of TRPC4 channels associated with erectile dysfunction in diabetes. (30th April 2014) - Sung, H. H.; Choo, S. H.; Ko, M.; Kang, S. J.; Chae, M. R.; Kam, S. C.; Han, D. H.; So, I.; Lee, S. W.
Summary In recent reports, an association between altered TRPC channel function and the development of various diabetic complications has drawn the attention of many investigators. The aim of this study was to investigate the expression of TRPC4 channels of corpus smooth muscle (CSM) cells in diabetes, and to evaluate the association between erectile dysfunction (ED) and altered TRPC4 channel function. The expression of TRPC4 in the penile tissue of human, normal and diabetic rat was investigated using RT‐PCR, western blotting and immunohistochemistry (IHC). In vivo gene transfer of dominant negative (DN) TRPC4 into the CSM of rat was conducted. In vivo pelvic nerve stimulation was performed to measure erectile function. Expression of TRPC1, TRPC3, TRPC4 and TRPC6 in human and rat CSM tissues was confirmed by RT‐PCR, western blot and IHC. In the diabetic rat, the expression levels of mRNA and protein of the TRPC4, and TRPC6 were significantly increased compared to control rats (p < 0.05). The change in TRPC4 expression in the diabetic rats was higher than those of the other TRPC subunits (p < 0.05). The IHC showed that only TRPC4 expression had a higher intensity in the diabetes compared to normal rats (p < 0.05). Gene transfection with TRPC4DN into the diabetic rats restored erectile function to levels similar to that of normal controls. Gene expression of TRPC4DN in CSM tissue was confirmed by RT‐PCR 2 weeks after transfection. This study demonstrated that TRPC4 channel expression increased in the penile CSM cells of diabetic rats. The down‐regulation of TRPC4 with DN form restored erectile function in the diabetic rats. The alteration of TRPC4 channel is one of pathophysiology of ED and could be a target for drug development for ED.